Muhamed Cicak - 1 year ago 67
C Question

# K&R Book 3-2 Exercise (escape function)

"Write a function escape(s,t) that converts characters like newline and tab into visible escape sequences like \n and \t as it copies the string t to s. Use a switch. Write a function for the other direction as well, converting escape sequences into the real characters." Is a Exercise 3-2 from K&R book. So i tried to do it. My escape function works properly. But my inverseescape is giving me the same answer as the escape function is giving. Here is the code:

``````#include <stdio.h>
#define MCC 100

void espace(int* str,int* t);
void inverseescape(int * str,int *t);
void getline(int*);

int main(void){
int firstarr[MCC];
int secondarr[MCC];
int thirdarr[MCC];
getline(firstarr);
espace(firstarr,secondarr);
printf("-----------AFTER ESCAPE------------\n");
for(int g=0;secondarr[g];g++){
printf("%c",secondarr[g]);
}
inverseescape(secondarr,thirdarr);
printf("\n-----------AFTER INVERSEESCAPE------------\n");
for(int g=0;thirdarr[g];g++){
printf("%c",thirdarr[g]);
}
return 0;
}

void getline(int* arr){
int i=0;
int c=0;
while((c=getchar())!=EOF){
arr[i]=c;
arr[i+1]=0;
i++;
}
}

void espace(int* string,int* target){
int i = 0;
int j = 0;
while(string[i]){
switch(string[i]){
case '\a':
target[j]='\\';
target[++j]='a';
target[++j]=0;
break;
case '\b':
target[j]='\\';
target[++j]='b';
target[++j]=0;
break;
case '\t':
target[j]='\\';
target[++j]='t';
target[++j]=0;
break;
case '\n':
target[j]='\\';
target[++j]='n';
target[++j]=0;
break;
case '\v':
target[j]='\\';
target[++j]='v';
target[++j]=0;
break;
case '\f':
target[j]='\\';
target[++j]='f';
target[++j]=0;
break;
case '\r':
target[j]='\\';
target[++j]='r';
target[++j]=0;
break;
case '\"':
target[j]='\\';
target[++j]='\"';
target[++j]=0;
break;
case '\'':
target[j]='\\';
target[++j]='\'';
target[++j]=0;
break;
case '\?':
target[j]='\\';
target[++j]='\?';
target[++j]=0;
break;
case '\\':
target[j]='\\';
target[++j]='\\';
target[++j]=0;
break;
default:
target[j]=string[i];
target[++j]=0;
break;
}
i++;
}
}

void inverseescape(int* string,int* target){
int i = 0;
while(string[i]){
switch(string[i]){
case '\\':
switch(string[i+1]){
case 'a':
target[i]='\a';
case 'b':
target[i]='\b';
case 't':
target[i]='\t';
case 'n':
target[i]='\n';
case 'v':
target[i]='\v';
case 'f':
target[i]='\f';
case 'r':
target[i]='\r';
case '\"':
target[i]='\"';
case '\'':
target[i]='\'';
case '\?':
target[i]='\?';
case '\\':
target[i]='\\';
}
default:
target[i]=string[i];
}
target[++i]=0;
}
}
``````

I am using switch statement first time (and probably last) so the code is not well-written (i guess).

Input:

shadow

of

the

beast

Output:

-----------AFTER ESCAPE------------

shadow\nof\nthe\nbeast

-----------AFTER INVERSEESCAPE------------

shadow\nof\nthe\nbeast

Answer Source

You're missing the `break` in the `inverseescape` case statement. `case`'s behaviour has the curious property of falling through to the statement below unless you explicitly `break` out of the `case`. In this case it's falling through to your `default` case and setting the output to the input.

Recommended from our users: Dynamic Network Monitoring from WhatsUp Gold from IPSwitch. Free Download